Gossypiboma: a surgical menace - Shah, Nitin H.; Joshi, Aditi V.; Shah, Vaishali N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Gossypiboma is a rare yet devastating complication. It may be a sequela to any kind of surgical procedure, however intra-abdominal surgeries are commonly implicated as the cause for this entity. In chronic cases, it may even lead to severe morbidity. We report a case of gossypiboma post vaginal hysterectomy, diagnosed and treated successfully by laparoscopy.